2017
DOI: 10.1016/j.parkreldis.2017.09.021
|View full text |Cite
|
Sign up to set email alerts
|

Genetic risk factors in Finnish patients with Parkinson's disease

Abstract: Introduction Variation contributing to the risk of Parkinson's disease (PD) has been identified in several genes and at several loci including GBA, SMPD1, LRRK2, POLG1, CHCHD10 and MAPT, but the frequencies of risk variants seem to vary according to ethnic background. Our aim was to analyze how variation in these genes contributes to PD in the Finnish population. Methods The subjects consisted of 527 Finnish patients with early-onset PD, 325 patients with late-onset PD and 403 population controls. We screene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 28 publications
0
16
0
Order By: Relevance
“…We also compared the ortholog list to genes that have been identified as candidate risk genes for any human α-synucleinopathy by examining genome-wide association or whole exome sequencing studies from MSA (X. Gu et al, 2018;Sailer et al, 2016), PD (Chang et al, 2017;Guo et al, 2018;Jansen et al, 2017;Li et al, 2018;Quadri et al, 2015;Robak et al, 2017;Sandor et al, 2017;Schormair et al, 2018;Shulskaya et al, 2018;Siitonen et al, 2017;Ylönen et al, 2017), or DLB (Guerreiro et al, 2018;Keogh et al, 2016;Peuralinna et al, 2015). In total, we found 30 transcripts with a mammalian ortholog that had also been identified in one or more of these studies (Table 7).…”
Section: Relevance Of the Drosophila Model For Mammalian α-Synucleimentioning
confidence: 99%
“…We also compared the ortholog list to genes that have been identified as candidate risk genes for any human α-synucleinopathy by examining genome-wide association or whole exome sequencing studies from MSA (X. Gu et al, 2018;Sailer et al, 2016), PD (Chang et al, 2017;Guo et al, 2018;Jansen et al, 2017;Li et al, 2018;Quadri et al, 2015;Robak et al, 2017;Sandor et al, 2017;Schormair et al, 2018;Shulskaya et al, 2018;Siitonen et al, 2017;Ylönen et al, 2017), or DLB (Guerreiro et al, 2018;Keogh et al, 2016;Peuralinna et al, 2015). In total, we found 30 transcripts with a mammalian ortholog that had also been identified in one or more of these studies (Table 7).…”
Section: Relevance Of the Drosophila Model For Mammalian α-Synucleimentioning
confidence: 99%
“…Variants in the GBA gene, encoding the lysosomal enzyme glucocerebrosidase (GCase), are among the most common risk factors for PD, found in 3%‐20% of PD patients from different populations . Recently, mutations in another lysosomal gene involved in sphingolipid metabolism, SMPD1 , which encodes the lysosomal enzyme acid sphingomyelinase (ASMase), have also been associated with an increased risk for PD . In the Ashkenazi Jewish population, specific Niemann‐Pick type A (NPA)‐causing SMPD1 mutations, p.L302P (also called p.L304P) and p.fsP330 (also called p.F333Sfs*52 or c.996delC), were associated with PD in 2 independent studies .…”
mentioning
confidence: 99%
“…In the Ashkenazi Jewish population, specific Niemann‐Pick type A (NPA)‐causing SMPD1 mutations, p.L302P (also called p.L304P) and p.fsP330 (also called p.F333Sfs*52 or c.996delC), were associated with PD in 2 independent studies . In addition, 2 studies in Chinese populations and 2 studies in European populations identified additional SMPD1 mutations and variants associated with PD …”
mentioning
confidence: 99%
See 2 more Smart Citations